If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.66x + -11 = 4 + x Reorder the terms: -11 + 0.66x = 4 + x Solving -11 + 0.66x = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -11 + 0.66x + -1x = 4 + x + -1x Combine like terms: 0.66x + -1x = -0.34x -11 + -0.34x = 4 + x + -1x Combine like terms: x + -1x = 0 -11 + -0.34x = 4 + 0 -11 + -0.34x = 4 Add '11' to each side of the equation. -11 + 11 + -0.34x = 4 + 11 Combine like terms: -11 + 11 = 0 0 + -0.34x = 4 + 11 -0.34x = 4 + 11 Combine like terms: 4 + 11 = 15 -0.34x = 15 Divide each side by '-0.34'. x = -44.11764706 Simplifying x = -44.11764706
| 15a+11=6d+4 | | Y^2+y=32 | | 2-(4x-8)= | | 6+bx=b-8 | | 9y-4=8 | | x-5x-24= | | -2(3x+7)+2= | | -(-3a+2a-a)= | | [(3x)/14]-[(3x)/1]=9 | | -2.9v-5.4=-3.4-2.9 | | 13q+15=12c+7 | | 5c-(40+c)=300 | | -5x+4y=40 | | H-13=8 | | 5(x-4)+3x=-2(x+10)+10x | | q=3m-3u | | Bt=10t | | y=-73898x+3E+06 | | 9.8x+85.71=-10.2x+85.19 | | x*2-144=0 | | 6n+13=3x+14 | | (2y/3)-(13/2)=1/6 | | 3y=2y+34 | | sin^2(x)-3sin(x)+1=0 | | -4x+15=x^2 | | 36x-96-15x-15+140-20x=80-20x-48x-30 | | 8+2w+w^2= | | 3n^2-16n+12=0 | | sin^2(2x)-3sin(2x)+1=0 | | 3(16-18)/2(10) | | (2v+1)(4+v)=0 | | .4(x+2)=1.4(x+1.5) |